Growth Promotion in Elephant Foot Yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) Consequent to Colonization by the Root Endophytic Fungus, Piriformospora indica - F.N. Femina; S.S.Veena; S. Karthikeyan; G.L. Sreelatha (JOURNAL OF ROOT CROPS, 2022)
Elephant foot yam (EFY) is widely cultivated in many states of India due to its high production potential; acceptability as a vegetable in many delicious recipes and use in Ayurvedic medicines. Piriformospora indica is an endophytic mycorrhiza like fungus which has shown pronounced growth promotional and disease suppressing activities in many crops. The potential of P. indica to colonize elephant foot yam roots was explored for the first time and growth promotion in elephant foot yam plants consequent to root colonization by P. indica was also studied. Among twelve solid media evaluated for growth, maximum radial growth of P. indica was obtained on cassava starch and wheat extract + Jaggery (9 mm day-1). Among the ten liquid media tested, maximum mycelial mass was observed in wheat extract + jaggery and wheat extract + PDA media. The colonization ability of P. indica in elephant foot yam (var. Gajendra) was studied by trypan blue staining and further confirmation of colonization was done by amplifying species specific Pitef1 gene. Incorporation of P. indica resulted in promotion of all growth parameters like shoot length, root length, biomass, girth, leaf area etc. of host plant. P. indica is known to inhibit many pathogens in various crops apart from causing growth promotion. Hence, studies on the effect of P. indica colonization on various diseases of elephant foot yam will help in tapping the full potential of the organism in organic cultivation of EFY